Global, regional, and national burden of leukemia, 1990–2021: a systematic analysis of the global burden of disease in 2021 - Chen, Jiaxi; Pang, Wenyi; Deng, Miao; Zheng, Rubin; Chen, Yanjin; Zhang, Ziyang; Tan, Zhouke; Bai, Zhixun (Frontiers in Medicine, 2025)
BackgroundLeukemia is a heterogeneous hematologic malignancy with varying incidence, mortality, and disability-adjusted life years (DALYs) worldwide. Although the burden of leukemia has declined over recent decades, substantial disparities remain across different regions, socioeconomic levels, age groups, and sexes. This study looks at trends in leukemia cases, deaths, and the impact on quality of life from 1990 to 2021, aiming to uncover inequalities and help design better interventions.MethodsThis study extracted data from the Global Burden of Disease (GBD) database (1990–2021) for five types of leukemia. The age-standardized incidence, mortality, and DALY rates for leukemia were calculated for 204 countries and 27 super regions worldwide. The estimated annual percentage change (EAPC) was used to quantify the trends in the leukemia burden, and trends were quantified using estimated annual percentage changes (EAPCs). Decomposition analysis examined the contributions of population growth, aging, and epidemiological changes. Additionally, autoregressive integrated moving average (ARIMA) and age-period-cohort (APC) models were employed. Inequality in leukemia burden was assessed using the Slope Index of Inequality (SII) and Concentration Index (CI).ResultsGlobally, the incidence and mortality of leukemia increased with age and were consistently higher in males. While incidence and mortality are projected to rise, DALYs are expected to decline slightly by 2031. Acute lymphoid leukemia (ALL) and acute myeloid leukemia (AML) dominated incidence and mortality patterns, with higher ALL burdens in low-SDI regions and more pronounced AML burdens in higher-SDI regions. Decomposition analysis indicated that epidemiological changes and population growth drove trends in incidence and mortality, respectively. APC results showed declining period effects and lower risks in more recent birth cohorts. Inequality analyses revealed a growing disparity in incidence and mortality burdens in high-SDI countries, while DALYs inequality slightly narrowed.ConclusionFrom 1990 to 2021, the global burden of leukemia has shifted, with persistent geographic, socioeconomic, and sex-related differences. Although overall improvements in prevention and treatment have reduced the DALYs burden, rising incidence and mortality in certain regions underscore the need for tailored public health strategies, early screening, and risk-based interventions to address persistent health inequalities and mitigate future leukemia burdens.